Pembelajaran Berdiferensiasi dalam Model Project-Based Learning: Kajian Literatur - Mutiah Syahidah; Kustiarini Kustiarini (Universitas Hamzanwadi, 2026)
Differentiated Instruction within the Project-Based Learning (PjBL) Model at the Elementary School/Madrasah Ibtidaiyah (SD/MI) Level is a strategic approach to addressing the diverse learning needs of students. This study aims to evaluate the integration of differentiated instruction with the PjBL model in order to enhance the effectiveness of student-centered learning. The research was conducted through a literature study using a qualitative approach, based on the analysis of 20 scholarly articles published between 2022 and 2025. Data collection was carried out by documenting relevant sources such as academic journals, books, and national education policy guidelines. The findings indicate that the integrated application of PjBL positively influences students’ academic achievement, motivation, creativity, independence, and mastery of 21st-century skills. This model also proves to support student-centered learning principles, as mandated by the Kurikulum Merdeka (Independent Curriculum). The implications of this study highlight the essential role of teachers in designing adaptive, relevant, and responsive instruction that acknowledges the diverse characteristics of students. In this way, differentiated PjBL can serve as a relevant and applicable learning strategy in elementary education